Chemically induced mice cough model - Riffat Farooqui (Journal of Bahria University Medical and Dental College)
Cough is the most common respiratory symptom that has been experienced by every human. Both the chemically and mechanically sensitive airway nerves take part in mediating the cough reflex and establishing synapses in the brainstem's caudal two-thirds of the nucleus tractus solitaries. The sensation of an "urge to cough" is ostensibly associated with activation of broncho- pulmonary C-fibers. These C-fiber nerves become directly activated, 'sensitized' or 'hyper-activated' by chemicals such as capsaicin, bradykinin, adenosine, prostaglandin type E-2 (PGE2), citric acid, hypertonic saline solution, Sulfur dioxide (SO2). Chemically induced cough facilitates the quantification of cough and the assessment of antitussive effects of specific therapeutic agents. Sulphur dioxide gas has been used to elicit cough in various experimental animals like cats, rats and mice.